Peranan Dark Septate Endophyte dalam Budidaya Tanaman - Andi Nur Cahyo (Fapetrik-UMPAR, 2021)
Dark Septate Endophyte (DSE) is a fungus in symbiosis with the host plant and is characterized by the presence of dark pigment, insulated hyphae, and microscleretia. The effect of DSE fungi on the host plant is specific according to the fungal strain, host plant species, and environmental conditions. DSE fungi can colonize host plant roots intra and extracellularly as well as ectendomycorrhiza. In DSE colonization, sometimes it fails to form a dense mantle and hartig net, but instead, it forms melanin microscleretia. The symbiosis between DSE fungi and suitable host plants can increase plant growth, uptake of N and P elements, resistance to drought, extreme temperatures, and protect plants from plant-disturbing organisms. The increase in the uptake of N and P elements was caused by the ability of DSE fungi to produce proteolytic enzymes and phosphatases that can mineralize organic N and P so that they become available to plants. Increased resistance to drought and extreme temperatures is thought to be due to melanin hyphae which can help absorb water from the soil and produce antioxidants and protection against free radicals. In addition, some strains of DSE fungi also produce chlorine to protect plants from plant-disturbing organisms.